Availability and Consistency Tradeoffs in the Echo Distributed File System - Hisgen, Andy; Birrell, Andrew; Mann, Timothy; Schroeder, Mike; Swart, Garret (Proceeding of the 2nd IEEE Workshop on Workstation Operating Systems, 1989)
Workstations typically depend on remote servers accessed over a network for such services as mail, printing, storing files, booting, and time. The availability of these remote services has a major impact on the usability of the workstation. Availability can be increased by replicating the servers. In the Echo distributed file system at DEC SRC, two different replication techniques are employed, one at the upper levels of our hierarchical name space, the name service, and another at the lower levels of the name space, the file volume service. The two replication techniques provide different guarantees of consistency between their replicas and, therefore, different levels of availability. Echo also caches data from the name service and file volume service in client machines (e.g., workstations), with the cache for each service having its own cache consistency guarantee that mimics the guarantee on the consistency of the replicas for that service. The replication and caching consistency guarantees provided by each service are appropriate for its intended use.